2019
DOI: 10.3390/min9020128
|View full text |Cite
|
Sign up to set email alerts
|

Ore Assimilation and Secondary Phases by Sintering of Rich and High-Gangue Iron Ores

Abstract: During the iron ore sintering process, two types of particles are present in the sinter bed: (1) fines, which are actively taking part in melting and the formation of secondary phases, and (2) coarse ores, which are partially interacting with the surrounding melt. The quality of the final sinter is particularly determined by the secondary phases and their bonding ability. Due to chemical differences between the fines and coarse particles, knowing the overall chemical composition of the sintering blend is not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…A study by Scarlett et al [17] suggests that the phase compositions in the sinter matrix structure consist of iron oxide by 35 to 60%, ferrites (mostly SFCA) by 20 to 45%, glassy phases by more than 10% and dicalcium silicates by more than 10%. They emphasize that the bond phase morphology is typically composed of SFCA phase composition as well as iron oxides and silicates, forming the most important bond phase structure since SFCA has a major impact on the quality properties of the sinter [18,19,26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Scarlett et al [17] suggests that the phase compositions in the sinter matrix structure consist of iron oxide by 35 to 60%, ferrites (mostly SFCA) by 20 to 45%, glassy phases by more than 10% and dicalcium silicates by more than 10%. They emphasize that the bond phase morphology is typically composed of SFCA phase composition as well as iron oxides and silicates, forming the most important bond phase structure since SFCA has a major impact on the quality properties of the sinter [18,19,26].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1-a) shows the typical sintering process of iron ore, fluxes and coke breeze. SFCA phases, calcium-rich ferrite structures, calcium silicates and glassy structures are observed within a typical sinter produced with ore grains in the sinter matrix [9,[14][15][16][17]. At low temperatures (<1220 °C) in the sinter body, assimilation is expected to be low and contains a significant amount of residual ore resulting in a heterogeneous texture.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the mineralogy of iron ore sinters is quite complex. 27) The characterisation of the phases in sinter is usually performed manually by an experienced mineralogist (point counting) using a microscope. 28) With the advancement of science and technology, there are an increased number of methods to characterise the composition and structure of mineral phases in sinter.…”
Section: Mineralogical Compositionmentioning
confidence: 99%
“…31) Iron oxides exist either in an unreacted primary form or as secondary phases formed by reactions or precipitation from the melt. 27,31) Hsieh and Whiteman [32][33][34] have found that the gas atmosphere used in sintering and the compositions of raw materials have significant effects on the mineral phases that are formed.…”
Section: Mineralogical Compositionmentioning
confidence: 99%
“…During the iron ore sintering process, two types of particles are present in the sinter bed: (1) fines, which are actively taking part in melting and the formation of secondary phases, and (2) coarse ores, which are partially interacting with the surrounding melt. (Mezibricky et al, 2019) METODOLOGY OF RESEARCH Today, efforts are being made to improve the quality of the agglomerate by reducing fuel consumption. High-quality fuel for agglomerate production is finegrained coke dust or coke pulp.…”
Section: Sintering Processmentioning
confidence: 99%